Quantitative gait analysis in patients with spinocerebellar ataxia—An explorative analysis - Tittu Thomas James; V SelvaGanapathy; Nitish Kamble; Pradnya Dhargave; Pramod K Pal; Kesavan Muralidharan (Annals of Movement Disorders, 2022)
BACKGROUND: Quantitative gait analysis is aimed at quantifying the degree of gait impairment in a patient. It helps to estimate the severity, track the prognosis, and identify the treatment effect in patients. There is a paucity of studies assessing gait characteristics in patients with spinocerebellar ataxia (SCA) using instrumental gait analysis. Here, we aim to identify the gait characteristics in patients with SCA and compare them with age-matched healthy individuals. METHODS: In this retrospective cross-sectional study, we analyzed the gait analysis data of patients with SCA from May 2018 to January 2020 in the gait and balance laboratory of the Physiotherapy Center in NIMHANS and compared them with age-matched controls from the existing database. The data were analyzed using an independent t-test. RESULTS: Each group consisted of 49 subjects. The SCA group had a mean age of 37.88 ± 13.25 years and the control group has a mean age of 40.88 ± 14.57 years, with a male to female ratio of 1:0.96 and 5:2, respectively. A significant difference was observed in all gait parameters (p < 0.001) between the SCA and control groups, except for swing time (p = 0.396). The SCA group demonstrated reduced velocity and cadence compared to the control group. The values of spatial parameters were reduced in the SCA group, with increased temporal parameters along with the base of support. The coefficient of variation was significantly increased in the SCA group, and the highest value was recorded for step length (10.45 ± 7.14). CONCLUSION: Patients with SCA demonstrated significant deviation in gait parameters from the normal values. The increased step-to-step variability in this patient population suggests an increased risk of falls. Identifying the changes in gait parameters at an early stage may help in planning the rehabilitation of patients with SCA, with focus on fall prevention strategies by targeting improvements in gait variability.